Geochemical insights from formation waters produced from Wolfcampian and Leonardian intervals of the Midland Basin, Texas, USA. (March 2023) - Nicot, Jean-Philippe; Darvari, Roxana; Smye, Katie M.; Goodman, Emery
Abstract: The lower Permian of the Midland Basin of West Texas consists of mudrocks with some tight sandstones and carbonate-dominated intervals (Wolfcamp and Spraberry formations) averaging a thickness of 975 m (3200 ft). They have been the target of a large revitalization of oil and gas production from the basin using hydraulic fracturing stimulation and horizontal well technology. Little is known about the aqueous geochemistry of these intervals. We sampled produced formation water from 53 wells across the basin and put them in the context of the basin flow history. Analyzing for major and minor elements and stable water and strontium isotopes, we determined that: (1) TDS values vary from 72 to 135 g/L, decreasing with increasing depth and increasing stratigraphic age; (2) ionic composition is consistent with that of Na–Cl brines found elsewhere in the basin with no major impact of meteoric input or halite dissolution as sometimes seen in the Permian Basin; (3) stable water isotopes (δ 18 O +5.0 ± 2.0‰ and δ 2 H −28 ± 5‰ VSMOW) are enriched; slightly radiogenic 87 Sr/ 86 Sr ratio is consistent with local carbonates. Interpretative results suggest that the modern resident brines of the low-permeability Lower Permian originated as Permian evaporative brines coeval with Upper Permian thick halite deposition. They would have dolomitized Permian carbonates in their gravity-driven downward migration and been further modified through water-rock interactions, including smectite-illite conversion. Highlights: Geochemical profiles: 53 hor. wells organized in 4 clusters representing 8 benches. TDS from 72 to 135 g/L, decreasing with increasing depth and stratigraphic age. Na–Cl brines, ∼no meteoric input, no halite dissolution, common processes. Geochemistry of each bench is different and discriminatory but part of a continuum. Wolfcamp C and D show strong evidence of illite-smectite conversion.